La campagna elettorale 2013 in TV: tanta politica, pochi temi e tre protagonisti - Valeria Bianchi; Cristina Chianale (QOE-IJES)
The paper provides an analysis of political communication on television during the 2013 general elections. 13 television programs of different types (news, information programs and infotainment) were monitored during the period 1 December 2012 - 3 March 2013 and data collected. The analysis was carried out with the support of a codebook consisting of 43 variables that refer to themes, electoral and political relevance, news and actors’ characteristics. The aim of this paper is to describe the campaign by the quantity of political information and the themes at the center of the debate, with particular attention to the similarities and differences between the various program types and television networks. Finally the visibility of the main leaders and the themes discussed during the entire period of the election campaign were analyzed.